Alto número de portadores leptospirais entre cães assintomáticos no município de São Gonçalo, região metropolitana do Rio de Janeiro, Brasil - Sant’anna, R.; Vieira, A. S.; Grapiglia, J.; Lilenbaum, W. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
The dog’s role as leptospire carriers has been increasingly studied, because there is strong evidence that asymptomatic dogs can be chronic carriers and can act as a source of infection for human beings, causing a public health problem.